Max–min fair Financial Transmission Rights payment‐based AC optimal power flow locational marginal price decomposition. Issue 10 (1st October 2014) - Bharatwaj, V. Naren; Abhyankar, Abhijit R.
Abstract : The decomposition of locational marginal price obtained from AC optimal power flow is disputable because of its dependency on the choice of energy reference. The dispute arises because the difference of congestion component, on which the Financial Transmission Rights (FTR) payments are made, is not constant and depends on the energy reference. Prior art aimed at obtaining reference‐independent decomposition. The authors look at this dispute as a fairness issue and formulate the decomposition as a fairness problem. The fairness issue is addressed by invoking max–min fairness criteria which ensures that the FTR payment (FP) received (made) is not at the expense of other ill‐positioned FTR holders. Max–min fairness algorithm is used to arrive at an energy reference choice that aims at maximising the FP of each FTR. This in turn ensures that revenue received (payment made) is the maximum (minimum) possible under the set of constraints, without adversely affecting the FP of other FTR holders. Results on PJM 5 bus and IEEE 30 bus systems indicate that a fair solution is indeed possible.